A stretchable hardness sensor for systemic sclerosis diagnosis. (July 2022) - Liu, Meng-Yang; Wang, Xiu-Yuan; Wu, Xue-Yan; Wen, Xiao-Hong; Wang, Yang; Wang, Jia-Cheng; Zhao, Xue-Feng; Zhang, David Wei; Yang, Ji; Lu, Hong-Liang
Abstract: Systemic sclerosis (SSc) is a multi-organ desmosis exhibiting the symptom of skin sclerosis. Due to the complexity of human skin, the assessment of skin sclerosis was traditionally implemented through palpation by a clinician, which has numerous limitations. Wearable flexible sensor is expected to open up new approaches for SSc diagnosis. Herein, a thin hardness sensor comprising a strain sensor and a pressure sensor was developed to assess the hardness of skin quantitatively. The strain sensor exhibited a gauge factor of 1.45 while the pressure sensor exhibited a considerable force sensitivity of 0.46 N -1 . The above two sensors were stretchable and bonded to yield the hardness sensor, which can be easily attached on touched material and deform with the touched material under external force. Results showed that the sensor was able to distinguish touched materials with different Young's modulus. A harder material can be identified by a larger sensor output. Furthermore, the sensor was mounted on the skin to compare and assess the hardness of a healthy person as well as a patient. Obvious hardening was found to occur on some locations of the patient's skin by the sensor, which was also verified by a commercial durometer. The reliable performance enables our hardness sensor highly promising in the diagnosis of SSc and meritorious to the design of wearable sensors. Graphical Abstract: ga1 Highlights: A strain sensor based on AgNW/CNT/PDMS (AgCP) composite is fabricated by embedding patterned AgNW/CNT networks into PDMS. A stretchable pressure sensor with Ag Flake/CNT/PDMS foam is done by drop-casting Pickering emulsion on AgCP electrode. The stretchable hardness sensor can sense the applied force and deformation simultaneously. The hardness sensor differentiates obvious hardened skin locations of a systemic sclerosis patient for the first time.